Isolated ovarian tuberculosis in an Immuno- competent woman in the post partum period: case report - Wondimu Gudu (BMC, 2018)
Abstract Background Pelvic tuberculosis is a rare form of extrapulmonary tuberculosis. It commonly involves the fallopian tubes and the uterus from a lympho-hematogeneous spread. The presentation of pelvic tuberculosis as an isolated ovarian abscess is extremely rare and is reported only twice. Case presentation a 25 yrs. old para III mother in the post partum period undergone laparotomy for suspected tuboovarian abscess/ovarian tumor after presenting with abdominal pain, pelvic mass and fever. Intra-operatively, Isolated right ovarian mass with caseation in the cavity but no significant pelvic adhesions was detected and right oophorectomy was done. Post operative Histopathology of surgical specimens revealed tuberculous leision and patient recovered well after anti-tuberculosis treatment. Conclusion Isolated ovarian tuberculosis is a very rare form of Genital Tuberculosis which should always be considered in the evaluation of a woman presenting with any adnexal mass in highly prevalent areas.